The Role of Accounting in Business Law Compliance: Regulatory and Implementation Perspectives in Indonesia - Raymond Fransiscus; Siti Junaidah Hasibuan (Manajemen: Jurnal Ekonomi USI, 2025)
The development that continues to occur in the Indonesian business world, requires every agency and organisation related to finance to implement and encourage the creation of a good accounting system in supporting compliance with business law. Accounting is the art of identifying, measuring, and reporting transactions and other events that are relevant to the need for information that is useful to users for economic decision making. This study aims to analyse how accounting can contribute to ensuring companies meet applicable legal regulations, as well as the challenges faced in its implementation in Indonesia. The research method used is literature study and document analysis, by examining various accounting regulations applied in Indonesia, such as Financial Accounting Standards (FAS), tax regulations, and company law. The results show that accounting has a significant role in ensuring transparency, accuracy, and accountability of corporate financial statements, which in turn supports compliance with legal regulations governing business aspects. However, there are a number of challenges in implementation, such as limited resources, uneven understanding of regulations, and weak supervision. This study suggests the need for increased training and socialisation on accounting regulations, as well as strengthened supervision by relevant authorities to ensure better legal compliance in business practices in Indonesia